War of Words : Dutch Pro-Boer Propaganda and the South African War (1899-1902) - Kuitenbrouwer, Vincent (Johan Jacob Vincent), 1978- (Book collections on Project MUSE., 2012)
"Between 1899 and 1902 the Dutch public was captivated by the war raging in South Africa between the Boer republics and the British Empire. Dutch popular opinion was on the side of the Boers: these descendants of the seventeenth-century Dutch settlers were perceived as kinsmen, the most tangible result of which was a flood of propaganda material intended as a counterweight to the British coverage of the war. The author creates a fascinating account of the Dutch pro-Boer movement from its origins in the 1880s to its persistent continuation well into the twentieth century. Kuitenbrouwer offers fascinating insights into the rise of organisations that tried to improve the ties between the Netherlands and South Africa and in that capacity became important links in the international network that distributed propaganda for the Boers. He also demonstrates the persistence of that stereotypes of the Boers and the British in Dutch propaganda materials had lasting effects on nation building both in the Netherlands and South Africa of the period"--Publisher's description.